2019
DOI: 10.1186/s13568-019-0839-9
|View full text |Cite
|
Sign up to set email alerts
|

Removing Disperse red 60 and Reactive blue 19 dyes removal by using Alcea rosea root mucilage as a natural coagulant

Abstract: In terms of health, dyes have carcinogenic, mutagenic and toxic properties and can have adverse effects on health and the environment. Therefore, sewage containing to dyes must be purified before being discharged into the environment. The current study aimed to investigate the effectiveness of Alcea rosea root extract in Disperse red 60 and Reactive blue 19 dyes removal from synthetic sewage. In this study, the effect of different indices including pH (5–11), Alcea rosea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…The various physical and chemical methods have been used to remove these compounds from aqueous media, including adsorption, optical decomposition, solvent extraction, or chemical oxidation 11,[14][15][16] . Some of them, Ni 2 Pd/KCC-1 and Fe 3 O 4 /CeO 2 have shown a high ability to remove this compound, and NiO/UV/H 2 O 2 was able to remove 100% 4-CP [17][18][19] .…”
mentioning
confidence: 99%
“…The various physical and chemical methods have been used to remove these compounds from aqueous media, including adsorption, optical decomposition, solvent extraction, or chemical oxidation 11,[14][15][16] . Some of them, Ni 2 Pd/KCC-1 and Fe 3 O 4 /CeO 2 have shown a high ability to remove this compound, and NiO/UV/H 2 O 2 was able to remove 100% 4-CP [17][18][19] .…”
mentioning
confidence: 99%
“…Nerium oleander plant also has ability to phytoextract the Cr and Ni heavy metals [29]. Alcea rosea plant has the potential to remove disperse red 60 and reactive blue 19 dye [30]. The major research work of screened plants is reported on the removal of heavy metals from the soil, as the T. erecta plant was used to remove Ni and Pb from the soil [31].…”
Section: Introductionmentioning
confidence: 99%
“…Glandularia pulchella explored to decolorize the dye green HE4B [24] and Ipomoea hederfolia ornamental plant able to decolorize the dye mixtures and scarlet red dye [25]. Alcea rosea plant has the potential to remove disperse red 60 and reactive blue 19 dye [26]. The researchers also explored the phytoremediation potential of Portulaca grandi ora [27], Blumea malcolmii [28], Typhonium agelliforme [29] etc for dye degradation in aqueous form.…”
Section: Introductionmentioning
confidence: 99%